P. G. Rhome, By-Laws of the Corporation of Crawfordville, Georgia 8 (1849) - (:unkn) unknown (My University, 1849)
Prohibited shooting or discharging any pistol, gun, rifle, or other fire-arms within the corporate limits. Violators fined not less than twenty-five cents nor more than one dollar on the first offense. Upon the second offense, violators fined not less than one dollar, nor more than two dollars, at the commissioners discretion.
Keywords: DISCHARGE